Analisis Pengaruh Leverage, Likuiditas, Total Asset Turnover, Dan Ukuran Perusahaan Terhadap Profitabilitas Perusahaan - Yoga Aji Nugroho; Nursiam (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study was to determine and analyze the effect of leverage, liquidity, total asset turnover, and company size on company profitability. The method used is a quantitative method for meganalysis of numerical data processed by statistical methods to test hypotheses. The population used in this study is a food and beverage sub-sector manufacturing company listed on the Indonesia Stock Exchange for the period 2021-2023. Sampling was carried out using the Purposive Sampling technique with the number of samples that met the requirements in this research amounting to 162 data. Based on the results of multiple linear regression analysis, it can be seen that leverage, liquidity, total asset turnover, and company size have an influence on company profitability.